Rejoinder: How methodological decisions impact the validity of moral content analyses. Issue 3 (3rd July 2021) - Hopp, Frederic R.; Weber, René
ABSTRACT: We herein discuss our commentary in light of Wang and Liu's response and clarify our suggestions regarding their original content analysis. Revisiting the methodological decisions that impact the reliability and validity of moral content codings, we focus on the selection and separation of coding and context units, the importance of keeping the annotations of codebook creators and coders independent for obtaining unbiased reliability estimates, the advantages of intuitive, context-aware text highlighting tasks executed by an optimally trained crowd, and on using the recommended moral dictionary scoring options when automatically coding textual documents. We thank Wang and Liu for their engagement with our commentary and in joining our efforts to improve guidelines for conducting reproducible, reliable, and valid moral content analyses.